Asymmetric polyethersulfone membranes modified with polyelectrolyte complexes: Morphology, thermal analysis and transport properties - da Silva Vale, Rayane [UNESP]; da Silva, Vanessa Bezerra; Contiero, Jonas [UNESP]; Knauss, Daniel M.; Paranhos, Caio Marcio (Department of Polymer Engineering, Scientific Society of Mechanical Engineering, 2024)
Mixing additives into a polymeric membrane constitutes an easy way to change their properties. Polyelectrolyte complexes (PECs) (polyelectrolytes combined via electrostatic interaction) are good materials for this due to their hy-drophilicity, tunable surface charge, and stable structure. In the present study, membranes containing PECs were obtained using three methodologies: complexation before, after, and during membrane formation. The chosen polyelectrolytes were 4-fluorophenyl sulfone-terminated poly(diallylpiperidinium hexafluorophosphate) and sulfonated poly(ethylene terephtha-late); the polymeric matrix was polyethersulfone. Fourier transform infrared spectroscopy confirmed the presence of PECs in the membranes. Scanning electron microscopy images of the membranes showed a dense skin and porous sub-layer, with variations in the thickness of the dense layer influenced by the presence of polyelectrolytes. The increase in water vapor permeability indicated that the complexes alter the hydrophilic profile of the membranes. The thermogravimetric curves showed different thermal behaviors depending on the interaction between the polyelectrolytes. All membranes demonstrated enhanced retention of Remazol red dye during filtration, with retention rates exceeding 95%. Notably, the Blend membrane exhibited the highest retention (over 98%) of the dye.
Keywords: phase inversion; poly(diallylpiperidinium); polymeric membrane; Remazol red dye; sulfonated poly(ethylene terephthalate)